12. März - Geburtstag von Paul Gerhardt (1607-1676) - Schroeter-Wittke, Harald (Woran sie glaubten - wofür sie lebten. 365 Wegbegleiter für die Tages des Jahres)

Walter Benjamin und Bertolt Brecht - Ansätze zu einer dialektischen Ästhetik in den dreißiger Jahren. - Müller, Inez

Theory for polarization-dependent four-wave-mixing signals in quantum wells - Meier, Torsten; Bennhardt, D.; Thomas, P.; Eccleston, R.; Mayer, E.; Kuhl, J. (Quantum Electronics and Laser Science Conference)
In degenerate four-wave-mixing (DFWM) experiments the polarization of the incident laser pulses can have a strong influence on the measured signal. For GaAs quantum wells a number of DFWM experiments were performed by using either parallel or perpendicular polarization of the incident laser pulses. Experimentally, it turned out that some characteristic features of the signal differ appreciably for the two configurations. In particular, different dephasing times, phase shifts of the quantum beats, different time-resolved behavior (echoes versus free-induction decay), and intensity dependence of the measured signal have been reported

Coherent coupling of exciton transitions in semiconductor quantum structures - Meier, Torsten; Koch, M.; Feldmann, J.; von Plessen, G.; Schulze, A.; Göbel, E.O.; Thomas, P.; Schmitt-Rink, S.; Shah, J.; Ploog, K.; Köhler, K. (Quantum Electronics and Laser Science Conference)
We investigate the coherent coupling of free and bound excitonic transitions, as wets as of distinct excitonic transitions arising from spatially separated quantum-well islands by means of time-resolved four-wave-mixing experiments.

Lie Semigroups and their Applications

Corwin, L. und F.P. Greenleaf. Representations of Nilpotent Lie Groups and their Applications. (Cambridge University Press, 1990) - Hilgert, Joachim (JBer. DMV)